2016
DOI: 10.1152/ajpgi.00372.2015
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of gastrointestinal and liver diseases. Animal models of acute and chronic pancreatitis

Abstract: Animal models of pancreatitis are useful for elucidating the pathogenesis of pancreatitis and developing and testing novel interventions. In this review, we aim to summarize the most commonly used animal models, overview their pathophysiology, and discuss their strengths and limitations. We will also briefly describe common animal study procedures and refer readers to more detailed protocols in the literature. Although animal models include pigs, dogs, opossums, and other animals, we will mainly focus on roden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 170 publications
(180 reference statements)
0
38
0
1
Order By: Relevance
“…The production of inflammatory cytokines such as TNF-α, IL-1β and IL-6 can promote and propagate the inflammatory reaction and injurious manner [39]. The attained data showed that the levels of TNF-α and IL-1β were down-regulated in the gut homogenate of Prednisolone treated rats more than Hypiran groups.…”
Section: Gross Appearance Of the Colonic Mucosa In Experimental Groupsmentioning
confidence: 88%
“…The production of inflammatory cytokines such as TNF-α, IL-1β and IL-6 can promote and propagate the inflammatory reaction and injurious manner [39]. The attained data showed that the levels of TNF-α and IL-1β were down-regulated in the gut homogenate of Prednisolone treated rats more than Hypiran groups.…”
Section: Gross Appearance Of the Colonic Mucosa In Experimental Groupsmentioning
confidence: 88%
“…Although they have the advantage of investigating responses in the absence of inflammation and changes in blood flow, their acinar cell phenotype disappears within hours of being placed in culture, making them useful for examining only early pancreatitis responses. Intact animal models of pancreatitis have been generated in many species including dogs, cats, guinea pigs, and even zebra fish 13, 14. Although many species have been used, rats and mice are used most commonly.…”
Section: Animal Models Of Clinical Acute Pancreatitismentioning
confidence: 99%
“…Nevertheless, a recent study showed a significant correlation of proteomic alterations in acinar cells in mice with caerulein-induced CP and human CP tissue, substantiating the caerulein model as a model of relevance for investigating the pathogenesis of CP (29). The main reasons for the model still being used widely are its ease of performance, its noninvasive methods, its high reproducibility and applicability in many species, and, currently, in transgenic and knockout mice, its aggravation of the present phenotype (11).…”
Section: Caerulein-induced Cpmentioning
confidence: 78%
“…Behavioral tests to examine pain were conducted in several studies, mostly in the framework of drug treatment studies (27,28), showing a significant increase in pain sensation compared with that in control animals. The pancreatitis induced in this model is considered mild, and pancreatic histology of the caerulein-treated mice normalizes after 3-6 wk (11). Furthermore, the clinical relevance of that model is questionable-although some patients develop CP from recurrent AP, the pathogenesis of human CP is not associated with hyperstimulation by cholecystokinin (4).…”
Section: Caerulein-induced Cpmentioning
confidence: 99%
See 1 more Smart Citation